A review on introduced Cichla spp. and emerging concerns. Issue 11 (November 2020) - Sastraprawira, Shantika Maylana; Abd. Razak, Iqbal Harith; Shahimi, Salwa; Pati, Siddhartha; Edinur, Hisham Atan; John, Akbar Bavajohn; Ahmad, Amirrudin; Kumaran, Jayaraj Vijaya; Martin, Melissa Beata; Chong, Ju Lian; Chowdhury, Ahmed Jalal Khan; Nelson, Bryan Raveen
Abstract: Peacock bass ( Cichla spp.) originates from the Neotropical environments of Brazil and Venezuela but, through trade and smuggling for aquarium keeping, sport fishing and aquaculture, it is now an emerging concern. Yet, less is known for Cichla spp. distribution and its ability to invade new environments. Aimed to communicate on Cichla spp. ecology, biology and introduction schemes from Scopus, Web of Science, Google Scholar and also National Centre for Biotechnology Information, this review also contains management strategies for invading fish species. While Cichla spp. can displace native fish populations, this concern is explained using ecological functions, physiological demands, direct and secondary invasion, disease tolerance and parasite spillover. Briefly, Cichla spp. has rapid embryogenesis (72 h) and matures in short periods (11–12 months), giving it an advantage to colonize new environments. With a large appetite, this true piscivore gains territorial control over water bodies by making it their feeding and nursery grounds. Perceived as an emerging concern after becoming introduced, seal-off or sport fishing were used to manage Cichla spp. but, this practice is not sustainable for the entire ecosystem. Hence, we recommend bottom-up management that involves community participation because they interact with the fish and have knowledge about their environment. Abstract : Cichlid; Peacock bass; Fisheries; Management; Ecology; Invasive; Animal physiology; Biodiversity; Ecosystem services; Environmental risk assessment; Nature conservation.